A Technological and Typological Analysis of Lithic Material from Skovmosen I, Denmark - Eggers-Kaas, Thomas; Pedersen, Jesper Borre; Hoggard, Christian Steven; Sauer, Florian; Hilgart, Jan; Riede, Felix (Danish Journal of Archaeology, 2019)
During road construction work, material attributed to the Final Palaeolithic was discovered at Skovmosen I, near Kongens Lyngby on Zealand, eastern Denmark. Although it is regularly mentioned in reviews of the southern Scandinavian Final Palaeolithic, the Skovmosen I assemblage has hitherto remained poorly described. We here review the site’s discovery history and its context. Aided by a three-dimensional digital recording protocol, this article details the assemblage composition and its technology. The assemblage is comprised of tanged points, scrapers and burins, alongside blades and cores as primary reduction products. Although evidently disturbed by the road construction that led to the site’s discovery, the material likely reflects the remains of a small Final Palaeolithic locale, where diverse activities were carried out.